"Historical whodunit", czyli wzloty i upadki brytyjskiej szkoły kryminału historycznego na przykładzie wybranych powieści Lindsey Davis = Lindsey Davis's historical whodunits, or the glories and the shortcomings of the british school of historical crime fiction - Kallas, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper offers an overview of a brief but rich and varied career of an intriguing subgenre of crimefiction - historical crime novel, or historical whodunit. This literary form came into being with Agatha Christie's 1945 novel "Death Comes as the End", and was further developed in the 1980s by the writers as diverse and talented as Ellis Peters, Anne Perry and Umberto Eco; it was finally established as a fully-fledged type of crime fiction in the 1990s with the works of Steven Saylor, John MaddoxRoberts, Boris Akunin and, last but not least, Lindsay Davis (a vigorous Polish school of historical crime, represented notably by Marek Krajewski, came into existence somewhat later). The paper offers an overview of a brief but rich and varied career of an intriguing subgenre of crimefiction - historical crime novel, or historical whodunit. This literary form came into being with Agatha Christie's 1945 novel "Death Comes as the End", and was further developed in the 1980s by the writers as diverse and talented as Ellis Peters, Anne Perry and Umberto Eco; it was finally established as a fully-fledged type of crime fiction in the 1990s with the works of Steven Saylor, John MaddoxRoberts, Boris Akunin and, last but not least, Lindsay Davis (a vigorous Polish school of historical crime, represented notably by Marek Krajewski, came into existence somewhat later).
Keywords: Davis, Lindsey (1949- ); literatura angielska - tematyka; powieść kryminalna